Triclopyr 3, 5, 6-trichloro-2-pyridinyl clean-up procedure from soil, sediment and water samples using SPE-HPLC-VWD - Tayeb, M.A.; Ismail Sahid,; Mardiana-Jansar, K.; Goh, Choo Ta; Afroza, Y.M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Triclopyr is a post emergence herbicide used to control woody plants. After application, the excess amount will enter the soil and water bodies and it is present in ppb level thus making extraction very difficult. The extraction of triclopyr 3, 5, 6-trichloro-2-pyridinyl residue from soil, sediment and water samples under different solid phase extraction (SPE) sorbent efficiency was studied for better recovery. Four different SPE sorbents i.e.: Oasis HLB, Water Sep-Pak, Cromabond (cation/anion PS-H+ /OH-), Isolute ENV+ and a series of solvent i.e. potassium dihydrogen phosphate (KH2PO4 0.1M), sodium hydroxide (NaOH 0.2M), potassium hydroxide (KOH 0.5 & 0.6M), ammonium acetate, methanol and water were used as extraction solution. Sample clean-up performance was evaluated using high performance liquid chromatography (HPLC, Agilent 1220 infinity LC) with variable wavelength detector (VWD) 290 nm. Cromabond®H+/OHcolumn with 0.6 M KOH was the most suitable for the clean-up in view of the overall feasibility of the analysis. The highest recovery was 89.32%.